2006
DOI: 10.1002/mabi.200600075
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles as a Versatile Platform for Optimizing Physicochemical Parameters for Targeted Drug Delivery

Abstract: The development of targeted vehicles for systemic drug delivery relies on optimizing both the cell-targeting ligand and the physicochemical characteristics of the nanoparticle carrier. A versatile platform based on modification of gold nanoparticles with thiolated polymers is presented in which design parameters can be varied independently and systematically. Nanoparticle formulations of varying particle size, surface charge, surface hydrophilicity, and galactose ligand density were prepared by conjugation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
124
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(127 citation statements)
references
References 41 publications
3
124
0
Order By: Relevance
“…100 Bergen et al have reported how different physicochemical properties, such as size, shape, PEGylation, or the ligand, regulate non-specific versus target-specific uptake. 101 Hackley et al 85 have reported the development of a cationic dendron with spherical carboxylic groups esterified with PEG and then, functionalized with quaternary ammonium end groups. These dendrons were used for the preparation of a positively charged gold nanoparticle-dendron conjugate and they were evaluated by in vivo and in vitro studies.…”
Section: Figure 4: Cartoon Depictions Of Some Possibilities For Ncds mentioning
confidence: 99%
“…100 Bergen et al have reported how different physicochemical properties, such as size, shape, PEGylation, or the ligand, regulate non-specific versus target-specific uptake. 101 Hackley et al 85 have reported the development of a cationic dendron with spherical carboxylic groups esterified with PEG and then, functionalized with quaternary ammonium end groups. These dendrons were used for the preparation of a positively charged gold nanoparticle-dendron conjugate and they were evaluated by in vivo and in vitro studies.…”
Section: Figure 4: Cartoon Depictions Of Some Possibilities For Ncds mentioning
confidence: 99%
“…Bergen et al [13] have used bare and nanoparticles covered bynonionic stabilizers based on PEG with diameters of 50, 80, 100, and 150 nm to study the biodistribution kinetics. Nonionic stabilizers provides particles without the charge.…”
Section: Particle (Stabilizer) Surface Effectmentioning
confidence: 99%
“…The arsenal of nanocarriers investigated for organelle specific targeting includes inorganic and organic materials. The major units of this arsenal are liposomes (Fattal et al, 2004), micelles (Bontha et al, 2006), quantum dots (QDs) (Hoshino et al, 2004), polymeric nanoparticles Yessine et al, 2004), gold nanoparticles (Bergen et al, 2006), magnetic nanoparticles (Xu et al, 2008), dendrimers (Samuelson et al, 2009), carbon nanotubes (Z. Yang et al, 2010 Nanocarriers are internalized into the cell by a process called endocytosis.…”
Section: Role Of Nanocarriers In Cytosolic Deliverymentioning
confidence: 99%